Children's understanding of animal, plant, and artifact properties between 3 and 6 years. Issue 6 (24th March 2017) - Fouquet, Nathalie; Megalakaki, Olga; Labrell, Florence
Abstract: We investigated the kinds of biological properties that children aged 3–6 years attribute to animals, plants, and artifacts by administering a property attribution task and eliciting explanations for the resulting property attributions. Findings indicated that, from the age of 3 years, children more frequently attribute properties to animals than they do to plants or artifacts. Moreover, attributions increased with age for animals, decreased for artifacts, and remained constant for plants. Concerning the conceptual development of animals and plants, results showed that the properties subtending children's initial conceptualization of animals are movement and nutrition, followed by growth, backed up by perceptual, biological, and categorical explanations. By contrast, for plants, the properties are growth and then movement, backed up by perceptual and biological arguments. These findings provide some support for the idea that both conceptual information and perceptual cues influence children's conceptual development. Highlights: This paper compares children's understanding of animals, plants, and artifacts between 3 and 6 years, in terms of property attributions and the spontaneous explanations of these objects. With a property attribution task, children more frequently attribute properties to animals than they do to plants or artifacts. Findings suggest that both conceptual information and perceptual cues influence children's conceptual development.